HUBUNGAN DUKUNGAN KELUARGA DENGAN MOTIVASI DAN PERILAKU LANSIA DALAM MENGIKUTI POSYANDU DI RW V PUSKESMAS DUPAK KOTA SURABAYA - Kurnia, Iqlima Dwi; Makhfudli, Makhfudli; Pratiwi, Denok Jua (JURNAL NERS LENTERA, 2018)
Introduction: Many problems to be faced by elderly, so they need serious attention as an effort to improve their welfare. One of efforts require family support for the elderly and also require to check the body health through Posyandu. This study aimed to explain correlation between family support with motivation and behaviour elderly in participating Posyandu elderly at RW 5 Puskesmas Dupak Surabaya City. Method: This study was a descriptive study using cross-sectional design. The population of this study are 119 elderly at RW 5, Dupak, Surabaya. Sampling technique was using simple random sampling and obtained 92 respondents. The independent variable was family support, and the dependent variable are motivation and behaviour elderly. Data were collected using questionnaire on family support, questionnaire on motivation elderly and observation data visited of elderly. Data were analyzed using Spearman Rho with a significance level of 0.05. Result: The results showed that majority of respondents had high family support, high motivation elderly for participanted Posyandu and elderly was active for visited in Posyandu. The result correlation between family support and motivation elderly showed p=0.000 and r=0.439, the correlation between family support and behaviour elderly showed p=0.000 and r=0.571. Discussion: Based on the analysis, it can be concluded that family support has positive correlation with motivation and behaviour elderly in participating Posyandu. In conclusion of this study, if family support high will have impact to high motivation and actived elderly for participanted Posyandu. Keywords: Family Support, Motivation, Behaviour, Elderly